Porphyry in fragments - Magny, Ariane (Routledge, 2016)
The Greek philosopher Porphyry of Tyre had a reputation as the fiercest critic of Christianity. It was well-deserved: he composed (at the end the 3rd c. A.D.) fifteen discourses against the Christians, so offensive that Christian emperors ordered them to be burnt. We thus rely on the testimonies of three prominent Christian writers to know what Porphyry wrote. Scholars have long thought that we could rely on those testimonies to know Porphyry's ideas. Exploring early religious debates which still resonate today, 'Porphyry in Fragments' argues instead that Porphyry's actual thoughts became mixed with the thoughts of the Christians who preserved his ideas, as well as those of other Christian opponents
Literaturverzeichnis Seite 157-176
Keywords: Porphyry; Eusebius; Jerome; Augustine; Against the Christians; De consensu Evangelistarum; Christianity